Synthesis and characterization of silver/clay nanocomposites by chemical reduction method - Ahmad, Mansor; Shameli, Kamyar; Darroudi, Majid; Wan Yunus, Wan Md. Zin; Ibrahim, Nor Azowa (Science Publications, 2009)
Problem statement: Silver Nanoparticles (Ag-NPs) have been synthesized by using chemical reduction method into the interlayer space of a Montmorillonite (MMT) as a solid support which is used to antibacterial application and polymer nanocomposites for fabrication of medical devices.